2012
DOI: 10.5455/vetworld.2012.723-726
|View full text |Cite
|
Sign up to set email alerts
|

Computer assisted semen analysis for quantification of motion characteristics of bull sperm during cryopreservation cycle

Abstract: Aim : The study was undertaken to quantify and to analyze the changes in the motion characteristics of bull spermatozoa during various stages of cryopreservation cycle. Materials and Methods: Using computer assisted semen analysis (CASA) technique, 26 ejaculates, collected from two Jersey bulls were analyzed for motility, head behaviour and swimming pattern of spermatozoa on dilution, pre-freeze and post-thaw stages of cryopreservation. French straw technique was employed for deep-freezing of semen using liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 5 publications
5
12
3
3
Order By: Relevance
“…Also the results of the viability and concentration assessment of semen were correct and similar to those obtained by Garner et al (1997). Thanks to the technological possibilities of computerized semen analysis, detailed motility parameters were analyzed that corresponded to the results obtained by Contri et al (2010) and Sundararaman et al (2012).…”
Section: Discussionsupporting
confidence: 62%
“…Also the results of the viability and concentration assessment of semen were correct and similar to those obtained by Garner et al (1997). Thanks to the technological possibilities of computerized semen analysis, detailed motility parameters were analyzed that corresponded to the results obtained by Contri et al (2010) and Sundararaman et al (2012).…”
Section: Discussionsupporting
confidence: 62%
“…Adoption of CASA technique has been reported as the potential tool for improvements in evaluation of semen to enhance fertility (Sundararaman et al, 2012). Hence, it is of great interest to use a combination of semen motion characteristics which can predict bull of high fertility performance more accurately than a single test.…”
Section: Introductionmentioning
confidence: 99%
“…However, Keshav (1996) reported significantly lower (65.22%) mean motility for Sahiwal breed than the current study. On the other hand, a higher mean motility percentage of 94.3% was reported by Sundararaman et al (2012) in Jersey bulls. In chilled semen though significant difference was not observed between Cross and HF; significantly lower motility percentage (57.90%) was observed in Boran.…”
Section: Discussionmentioning
confidence: 76%
“…Though the total and progressive motility percentages of this study lies in the ranges of total and progressive motility percentages of Keshav (1996); her mean values were higher than this study finding. Sundararaman et al (2012) also reported a higher motility percentage for chilled (89.4%) and frozen (63.0%) semen in Jersey bulls. These possible variations between studies could be due to the reasons stated above for fresh semen.…”
Section: Discussionmentioning
confidence: 81%